Small town girl - Spencer, LaVyrle (New York : Jove Books, 1998)
"Eighteen years ago, Tess McPhail left her tiny hometown of Wintergreen, Missouri, for the bright lights of Nashville and never looked back. Now one of country music's biggest stars, 'Mac' is a hardworking woman with little time for a personal life--until her sisters insist she come home to help care for their widowed mother. The welcome Mac receives is less than warm, especially from her former next-door neighbor Kenny Kronek. With a teenage daughter to raise, the handsome divorce refuses to give Mac the time of day. But when Mac discovers that Kenny's daughter is a promising country talent, she begins mentoring the girl in the music of love--and opening her own hardened heart to a man who makes her soul sing..."--
Keywords: Country musicians -- Fiction; Women singers -- Fiction; Musical fiction; Missouri -- Fiction; Nashville (Tenn.) -- Fiction; Musical fiction; Love stories